2018
DOI: 10.1021/acssynbio.8b00191
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Heterologous Gene Expression with Portable mRNA-Stabilizing 5′-UTR Sequences

Abstract: RNA half-lives are frequently perceived as depending on too many variables, and transcript stability is generally missed as a checkpoint amenable to manipulation in synthetic designs. In this work, the contribution of mRNA stability to heterologous protein production levels in E. coli has been inspected. To this end, we capitalized on the wealth of information available on intrinsic mRNA stability determinants, four of which were formatted as portable modules consisting of 5'-untranslated regions (UTRs). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Lou et al integrated hairpins in both ribozymes used in this work, RiboJ and VtmoJ, to expose the RBS and confirmed their catalytic functionality through rapid amplification of cDNA 5 ′ -ends (Lou et al, 2012). The presence of such hairpins in the 5 ′ UTR region was reported to increase the respective mRNA half-life, which leads to higher protein production (Viegas et al, 2018). Further clarification of the stabilizing effect of the hairpin structure of RiboJ and its individual effect on protein expression has been published elsewhere (Clifton et al, 2018).…”
Section: Qpcr Based Elucidation Of Mrna Stabilitysupporting
confidence: 58%
“…Lou et al integrated hairpins in both ribozymes used in this work, RiboJ and VtmoJ, to expose the RBS and confirmed their catalytic functionality through rapid amplification of cDNA 5 ′ -ends (Lou et al, 2012). The presence of such hairpins in the 5 ′ UTR region was reported to increase the respective mRNA half-life, which leads to higher protein production (Viegas et al, 2018). Further clarification of the stabilizing effect of the hairpin structure of RiboJ and its individual effect on protein expression has been published elsewhere (Clifton et al, 2018).…”
Section: Qpcr Based Elucidation Of Mrna Stabilitysupporting
confidence: 58%
“…Inspired by previous studies that demonstrated that naturally occurring stabilizers can be used to tune gene expression in synthetic gene circuits 31 , 33 , we inserted the 5’ UTR sequence from the E. coli ompA transcript between the promoter and RBS region to tune downstream GFP expression 20 , 34 , 35 ( Fig. 1a , right).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli , the endonucleases RNase E or RNase III target the underlying RNA molecule for primary cleavage followed by complete degradation via 3’ → 5’ exonucleases 27 29 . Previously discovered naturally occurring 5’ UTRs, termed RNA stabilizers, or rationally designed synthetic DNA cassettes can increase RNA half-life by forming 5’ secondary structures 30 33 . These 5’ hairpin structures have been shown to be able to control heterologous mRNA half-life and used to regulate recombinant protein expression without introducing stress to host cells 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ribonucleases have a fundamental role in the turnover of RNAs since the accumulation of degradation products and aberrant transcripts is usually quite detrimental for the cell; furthermore, they actively participate in the recycling of valuable nucleotides. Engineering and modulating the lifespan of RNAs has great potential (Viegas et al, 2018) and will certainly be one of the highlights of future science. Synthetic Biology supported by all the recent RNA-derived technologies will lead to important Biotech applications.…”
mentioning
confidence: 99%